Synthesis of BaZrS3 and BaS3 Thin Films: High and Low Temperature Approaches - Tim Freund; Sumbal Jamshaid; Milad Monavvar; Peter Wellmann (Crystals, 2024)
Current research efforts in the field of the semiconducting chalcogenide perovskites are directed towards the fabrication of thin films and subsequently determine their performance in the photovoltaic application. These efforts are motivated by the outstanding properties of this class of materials in terms of stability, high absorption coefficient near the band edge and no significant health concerns compared to their halide counterparts. The approach followed here is to use stacked precursor layers and is adopted from other chalcogenide photovoltaic materials like the kesterites and chalcopyrites. The successful synthesis of BaZrS3 from stacked layers of BaS and Zr and annealing at high temperatures (~1100 °C) with the addition of elemental sulfur is demonstrated. However, the film shows the presence of secondary phases and a flawed surface. As an alternative to this, BaS3 could be used as precursor due to its low melting point of 554 °C. Previously, the fabrication of BaS3 films was demonstrated, but in order to utilize them in the fabrication of BaZrS3 thin films, their microstructure and processing are further improved in this work by reducing the synthesis temperature to 300 °C, resulting in a smoother surface. This work lays the groundwork for future research in the fabrication of chalcogenide perovskites utilizing stacked layers and BaS3.